Making health systems work in low and middle income countries : textbook for public health practitioners - Siddiqi, Sameen; Mataria, Awad; Rouleau, Katherine D.; Iqbal, Meesha (Cambridge University Press, 2023)
"1. Health Systems from Unfamiliarity to Inevitability During the 1970s and 80s, debates within countries and in many international forums indicated a growing dissatisfaction with the state of health and health services. This was accompanied by a broad recognition that the solution needed to include the development of comprehensive national health systems,[1] a perspective further supported by the Alma Ata Declaration on Primary Health Care as the leading strategy for Health for All.[2] While scholarship on strengthening health systems has continued since, questions of what is a health system, what are its boundaries and components, how it should be analyzed, and how to best improve health system performance remain contested and evolving matters. Early work on health systems was influenced by Milton Roemer's descriptive analysis of national health systems,[3] while the subsequent reports by WHO in 2000 and 2007[4, 5] helped solidify a shared understanding of health system functions, goals and objectives"--